(untitled) (Iraqi National Journal of Earth Science (INJES), 2026)
The sequence ofthe Avana Formation (Late Eocene) has been studied in two outcrop sections in northern Iraq. The first section is (8m.) thick and located in the Aqupan area at the north plunge of Safin Anticline near the Shaqlawa region, while the second section is (57m.) thick and located in the Dohuk region at Bekhear Anticline. The succession of formations in both sections is composed of limestone, dolomitic limestone, marly limestone, marl, and black shale. The study recorded some sedimentary structures in some parts of the formation section such as lenticular and flaser bedding as well as herring bone cross-bedding. The lower contact of the formation is unconformable with the Gercus formation, while the upper contact of the formation appears to be conformable with the Pila Spi Formation. According to petrographic analysis, the formation rocks contain skeletal grains of the benthic foraminifera (such as miliolids and rotaliids), and larger forams (such as alveolinids), in addition to mollusca and green algae. The bioclastis of all these organisms well as non- skeletal grains as peliods and lithoclast. The matrix consists of micrite. The formation sequences have shown effects of digenesis processes such as dolomitization, cementation, Silicification, recrystallization, dissolution, physical and chemical compaction, micritization and Authigenesise .Facies analysis studies have shown that the sequences of Avana Formation consist of three main microfacies: lime mudstone, lime wackstone and lime packstone. These microfacies are further subdivided into eight submicrofacies. In addition, six other lithofacies are as follows: herring bone cross-bedding limestone lithofacies, flaser and lenticular bedding limestone lithofacies,madcrack limestones lithofacies, Lamination limestone lithofacies Stromatolites limestones lithofacies، and shale lithofacies.The results of facies analysis indicated that the formation was deposited in a tidal flat environment. Facies analysis revealed that the lower parts were deposited in subtidal environments, the middle parts in intertidal environments, and the upper parts in supratidal flat environments. That is, the formation was deposited in an upward-shallowing facies.